Applying APOS Theory to Enhance Algebraic Logic Skills: Comparing Traditional Teaching and Computer-Assisted Instruction - Longe, Idowu Oluwaseun; Maharaj, Aneshkumar (Indonesian Journal of Science and Mathematics Education, 2023)
This study aims to assess how effectively applied science students use equations to express connectivity in algebraic logic and understand their cognitive framework. This research measures students' understanding of mathematical logic connectors in line with the polytechnic curriculum and uses APOS theory as a basis. It compares the effectiveness of traditional teaching methods with the computer-assisted instruction (CAI) approach. The results show that students learning with CAI perform better in applying connectivity equations. These findings underscore the importance of students' cognitive schemes in understanding the relationship between algebra and logic. Students with a more mature conceptual understanding tend to overcome conceptual application difficulties better. For future research, it is suggested to explore the application of CAI methods in various learning contexts and other disciplines, as well as to assess its long-term impact on students' cognitive skills and mathematical understanding. Additionally, it is essential to compare the effectiveness of CAI with other innovative learning methods to determine the best approach to developing students' logic and algebra skills.